(untitled) (Genius Repository, 2023)
Merdeka Belajar is a term for the policy of Education and Culture Ministry to ensure that students experience independence in the learning process. The Merdeka Belajar policy coveres 4 components, a) The National Examination is changed by an Assesment of Minimum Competency and Character Survey for students, b) The National Standardized School Examination is granted authority to the school, c) The Lesson Plan simplification, and d) In the new students admission, expanded zoning system (covering 3 areas; Frontier, Remote and Disadvantaged Areas). The policy must be well understood by the teachers for Islamic Religious Education in each education level units. As a result, the activity for Islamic Religious Education Teachers Capacity Building in Semarang City was carried out. The training and mentoring produced two main products, the learning objectives flow and the learning module for the Islamic Religious Education subject.